Health-related quality of life in adults with transfusion-independent thalassaemia intermedia compared to regularly transfused thalassaemia major - Musallam, Khaled M. (2011)
Background: In patients with β thalassaemia intermedia (TI), the milder anaemia and transfusion independence imply better health-related quality of life (HR-QoL). However, the unbalanced pathophysiology of the disease allows for several serious clinical complications to manifest, which may have a negative impact on HR-QoL. Methods: This was a cross-sectional study on adult patients with transfusion- and iron chelation-independent TI and β thalassaemia major (TM) attending the Chronic Care Center, Hazmieh, Lebanon. A total of 80 patients agreed to participate in the study [32 TI (median age 24 yr) and 48 TM (median age 23 yr)]. The RAND SF-36 survey was used to assess HR-QoL. Data on patient demographics, clinical complications and socioeconomic status were collected. Results: Patients with TI and TM were comparable with age and gender, but patients with TM had a significantly longer median duration with a known thalassaemia diagnosis. Patients with TI had a higher proportion of multiple complications. Socioeconomic parameters were comparable, except for patients with TI being more commonly married. The mean Total, Physical Health and Mental Health Scores were significantly lower in patients with TI compared to TM, indicating poorer HR-QoL. There was a statistically significant positive correlation between the duration with a known thalassaemia diagnosis and a higher Mental Health Score (rs = 0.73, P = 0.020). The mean Physical Health Score was significantly lower in patients with multiple clinical complications compared to patients with single or no complications (P = 0.012). Associations remained independently significant at multivariate analysis. Conclusion: Patients with transfusion-independent TI have lower HR-QoL compared to TM patients. At a comparable age, the shorter duration since diagnosis and the multiplicity of complications may explain these findings.